Determination of Potential Drug-Drug Interactions Using Various Software Programs in a Community Pharmacy Setting - OKUYAN, BETÜL; SANCAR, MESUT (TURKISH PHARMACISTS ASSOC, 2019)
Objectives: The aim of the present study was to compare various software programs in detecting potential drug-drug interactions in a community pharmacy setting. Materials and Methods: Details of prescriptions were collected from 50 community pharmacies located in Istanbul in March and April 2015 (two days per week). From each pharmacy, the first 20 prescriptions that included more than one drug were collected to evaluate potential drug-drug interactions. The following software programs were utilized to detect potential drug-drug interactions: micromedexsolutions.com , medscape.com , and drugs.com . The number of potential interactions detected by the software programs was determined. Results: At least one potential drug-drug interaction was detected in 39.2% of the 1000 prescriptions by one of the software programs. According to the rates of total drug-drug interactions gathered from various software programs, these programs gave the following results: medscape.com 33.3%, drugs.com 31.3%, and micromedexsolutions.com 21.2%. Conclusion: After comparing different software programs, the potential drug-drug interactions found by the programs proved to be different. Therefore, we recommend that pharmacists confirm with a different program before making a decision when they detect clinically significant potential drug-drug interactions.
Keywords: Drug-drug interactions; software programs; community pharmacy; pharmacist; INTERACTION ALERTS; COMPENDIA; INFORMATION; RECOMMENDATIONS; CONSISTENCY; MANAGEMENT; WARFARIN